PENGARUH FAKTOR DEMOGRAFI, RISK TOLERANCE DAN OVERCONFIDENCE TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI MAHASISWA DI KOTA PEKALONGAN - Lathifatunnisa; Asri Nur Wahyuni (Politeknik Ubaya, 2021)
The purpose of this study was to obtain empirical evidence about the influence of demographic factors, risk tolerance and overconfidence on investment decision making with the object of research being students in Pekalongan City. This study uses quantitative data by taking a sample of 100 student respondents using purposive sampling technique. The distribution of questionnaires was chosen as the data collection method in this study. Multiple linear regression analysis, classical assumption test and hypothesis testing using SPSS 25 program were used as analytical tools in this study. The results of this study indicate that demographic factors, namely age, gender and monthly income have a positive but not significant effect on investment decision making, risk tolerance has a significant positive effect on investment decisions. On the other hand, overconfidence has a positive but not significant effect on investment decision making.